Síndrome hepatopulmonar (SHP): estudo prospectivo para avaliar a progressão da hipoxemia em pacientes candidatos ao transplante de fígado - Melo, Elisabete de (2006)
Hepatopulmonary syndrome (HPS), caused by abnormal intrapulmonary vasodilatation (IPVD), when associated with severe hypoxemia has been related to increased morbid-mortality in liver transplant candidates. The progression of hypoxemia in cirrhotic patients with IPVD is not well known. The aim of this study is to determine the probability of developing hypoxemia (Pa02 <70mmHg) in IPVD patients waiting for liver transplantation over two years. Thirty-two transplant candidates with IPVD detected by contrast-enhanced echocardiography (GI) were prospectively studied and the Pa02 of then was measured at the start and at the end of 12 and 24 months. Eleven patients without IPVD were taken as control group (GII). Paired t test showed that mean Pa02 was significantly lower at 24 months compared with basal mean at GI (78,5 ± 18,9 vs 94,05 ± 14,9; p=0,001). GI patients had significantly lower mean Pa02 at 12 months (84,6 ± 14,8 vs 95,7 ± 7,3; p=0,003) and at 24 months (78,5 ± 19,0 vs 88,7 ± 7,1; p=0,036) compared with GII patients. The Kaplan-Meier estimated ratio for the appearance of hypoxemia was approximately 10% ±5% at 12 months and 28% ± 10% at 2 years. The mean variation for Pa02 in GI patients was 4,6±13,4mmHg at 12 months and 15,5±15,5mmHg at the end of two years. There was no appearance of either hypoxemia or IPVD in GII patients. The variables: age, Child-Pugh score, smoking habit, pré-transplant Pa02 and PaC02 values did not discriminated patients who presented hypoxemia during the period of two years study. In conclusion, we demonstrate prospectively the progressive course of HPS, even on it s subclinical stage; the estimated risk for the appearance of hypoxemia in patients with IPVD was at least 30% at the end of 2 years. The identification of the early appearance of hypoxemia can lead to a better understanding of the hepatopulmonary syndrome natural history and may be helpful to optimize timing and to predict the outcomes of liver transplantation.